THE ROLE OF THE DENPASAR STATE PROSECUTOR'S OFFICE IN OVERCOMING CORRUPTION CASES IN DENPASAR-BALI - Ary Mahadnyani, Tjokorda Mirah; Juwita Arsawati, Ni Nyoman (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Corruption is an extraordinary crime (extraordinary crime), so far Criminal Corruption has caused damage in various aspects of the life of the community, nation, and state, therefore the eradication of corruption must be carried out continuously which must be carried out so that with this principle justice can be felt by the community. Law enforcement in Indonesia, which has been carried out to narrow the space for conventional corruptors, has proven to have experienced various obstacles that make people distrust the future of law enforcement in Indonesia, especially in terms of eradicating corruption. The Indonesian government seeks to eradicate corruption crimes by enforcing criminal laws related to corruption through the institution of the Judiciary tasked with supervising and enforcing the rule of law. Judicial power given to the Denpasar State Prosecutor's Office by the State of Indonesia to punish corruptors through investigations, audits, arrests, trials, and others.